Analysis of the difference between the subjective load intensity perception and real heart rate of male and female players in handball training - Bilka, J.; Hulka, K.; Safar, M.; Weisser, R.; Duskova, L.; Kristek, J. (Acta Universitatis Matthiae Belii, Physical Education and Sport, 2015)
Heart rate is the most frequently used sign for intensity of the load in physical activity. One of the alternative forms to determine the intensity is subjective evaluation of an athlete. Subjective evaluation of the intensity of the load can influence the effectiveness of the training process. The presented study deals with the use of Borg scale (CR-10) in adolescents in training handball. The research was conducted in a group of 32 female handball players in the three training sessions. It was performed as subjective evaluation of intensity loads and also as monitoring heart rate using heart rate monitors Team Polar2. The results showed that the median dependence (r = .63) between the subjectively perceived fatigue and actual heart rate. This dependence has occurred in the subjective assessment of the intensity of the load in boys (r = .47), but the girls demonstrated much closer dependence (r = .71). The boys showed the tendency to overrate while girls underrate the intensity of the load.